1970
DOI: 10.3329/jbau.v6i2.4838
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the status of use of chemicals and antibiotics in freshwater aquaculture activities with special emphasis to fish health management

Abstract: The study was carried out to understand current status of use of chemicals and antibiotics in fish health management in freshwater aquaculture activities. Data were collected through questionnaire interview, personal contact, market survey and participatory rural appraisal like focus group discussion with fish and prawn farmers, retailers of animal medicine and representatives of pharmaceutical companies. A range of chemicals including antibiotics were found available in market. Fish health management and dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 1 publication
5
50
0
Order By: Relevance
“…From the research findings of Hasan (2014) and Ahmed et al (2014) in Bangladesh there 7 categories and 34 types of chemicals used in aquaculture. Chemicals were used as pond preparation, disinfection, oxygen supplement, growth promotion, antibiotics and disease treatment which were nearly similar to the findings of Faruk et al (2008), Hasan (2014) and Ahmed et al (2014). In the present investigation it was recorded that 82% farmers used chemicals during pond preparation, 32% farmers used oxygen supplier, 55% farmers used growth promoters and 58% used chemicals for disease treatment (Figure 1).…”
Section: Present Status Of Aquaculture-drugs and Chemicals Used In Thsupporting
confidence: 65%
See 2 more Smart Citations
“…From the research findings of Hasan (2014) and Ahmed et al (2014) in Bangladesh there 7 categories and 34 types of chemicals used in aquaculture. Chemicals were used as pond preparation, disinfection, oxygen supplement, growth promotion, antibiotics and disease treatment which were nearly similar to the findings of Faruk et al (2008), Hasan (2014) and Ahmed et al (2014). In the present investigation it was recorded that 82% farmers used chemicals during pond preparation, 32% farmers used oxygen supplier, 55% farmers used growth promoters and 58% used chemicals for disease treatment (Figure 1).…”
Section: Present Status Of Aquaculture-drugs and Chemicals Used In Thsupporting
confidence: 65%
“…According to Faruk et al (2008) and Subasinghe et al (1996) lime, urea and TSP were important for the proliferation of algae. In the present study, farmers also used some commercial drugs for gas removal such as geotox and zeolite having positive effect of 80% and 85% respectively (Table 1).…”
Section: Effect Of Aquaculture-drugs and Chemicals In The Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover Aqua Savor and Aqua Grow-P were used against malnutrition as well as to improve health of fish. Faruk et al (2008) observed that Aqua Boost and AC Mix Super-Fish also had disease preventing ability in fishes. The authors farther mentioned that growth promotors like Vitamins, Minerals and Phospholipids enhanced in growth and survival of cultured fishes.…”
Section: Chemicals Used For Growth Promoter In Study Areamentioning
confidence: 93%
“…Disinfectants are widely used in many spheres of aquaculture. They are used both in hatchery and grow-out systems mainly for equipment cleaning, to maintain hygiene and in some cases to treat disease (Table 4) [56].…”
Section: Chemical Substancesmentioning
confidence: 99%